PENDEKATAN BEHAVIOR TERHADAP EFIKASI DIRI - Nur Hasan (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2016)
The purpose of this study is to determine the correlation of behavior approach toward self-efficacy. Subjects of this study totaled 35 students. Data collected by behavior approach scale (operant conditioning) and self-efficacy scale. Analisis that used in this research is the statistical data analysis by the number of data pairs of product moment correlation. Based on the analysis turned out the value of r xy = 0.394. This number is greater than the significance level of 5% = 0.334 to N = 35. It means significant that the null hypothesis reads "there is no correlation between behavior approach toward self-efficacy of students" (rejected). So there is correlation between behavior approach (operant conditioning) toward self efficacy of students.